If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 5.1x + 0.3x Combine like terms: 5.1x + 0.3x = 5.4x 0 = 5.4x Solving 0 = 5.4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5.4x' to each side of the equation. 0 + -5.4x = 5.4x + -5.4x Remove the zero: -5.4x = 5.4x + -5.4x Combine like terms: 5.4x + -5.4x = 0.0 -5.4x = 0.0 Divide each side by '-5.4'. x = 0 Simplifying x = 0
| 8x+12(x-9)=82 | | 1x^2-3x-12=0 | | -16t^2+288t-512=0 | | 12-2x=12+2x | | x^4=4x | | 2x+1+3(x-6)=23 | | 2x+6=69+-5x | | 0.5(3x-5)=8 | | 6(x-1)=3(x-2) | | 2/-4/3=x | | 2/-4/3 | | 5+7(x+1)=12+10x | | x+3/4=17/18 | | 2(x+2)=1x-5 | | -10-9y=-13 | | 4/6x-2/6 | | 8/9*4/5 | | 7x-12x=-45+15 | | 4(y-3)-2y=5(3y+1) | | x-1=2(3x+7) | | 21-9x=4x+8 | | 3/6x-9/18 | | 64/1*7/8 | | 6x-5=4x-9 | | 3/4x-1+1/2x=7/16x+1/8 | | 1/2(x-6)=9 | | 5(y-4)=2(y+5)Y | | f(x)=x^3-x^2-11x+3 | | 5/6*2/3*2/7 | | x=(2.4e)/(0.68^1/5) | | 3/5*4/7*1/3 | | -9x^2+16x-14=0 |